Temperatura e substrato para a germinação de sementes de Piptadenia moniliformis Benth. - de Azeredo, Gilvaneide Alves; de Paula, Rinaldo Cesar [UNESP]; Valeri, Sergio Valiengo [UNESP] (Ipef-inst Pesquisas Estudos Florestais, 2011)
In germination tests, substrate and ideal temperature are important for providing favorable conditions for the germination of seeds and the eventual development of seedlings. This research aimed at evaluating the effects of temperature and substrate on the germination of Piptadenia moniliformis Benth seeds. Two trials were done. In the first, seeds were submitted to germination under constant temperatures of 5 to 40 degrees C (increases of 5 degrees C) and alternated temperatures of 20-25, 25-30, 30-35, 20-30, 25-35 and 20-35 degrees C on paper. In the second trial, temperatures of 25, 20-30 e 20-35 degrees C were used in the substrates on (OP) and between paper (BP), on (OS) and between sand (BS), on (0V) and between vermiculite (BV) and paper roll (PR). The following traits were evaluated: percentage of seeds with protrusion of primary root and normal seedlings; speed germination index; length of primary root and of the hypocotyls and the dry mass of seedlings. A completely randomized design was used with 14 treatments. In the first experiment and a factorial scheme of 7 x 3 (7 substrates and 3 temperatures) was used in the second with four replicates of 25 seeds each. In the first experiment the constant temperatures of 25 e 30 degrees C and the alternated of 20-30 e 20-35 degrees C provided best results for the germination of seeds. In the second, the temperature of 25 C associated with the substrates BP, BS and BV surpassed the other treatments proving adequate for carrying out the germination tests of Piptadenia moniliformis Benth seeds.
Temperature and substrate for the germination of Piptadenia moniliformis Benth. seeds
Keywords: Piptadenia moniliformis Benth; honey-tree species; seed analysis